Numerical solution on MHD stagnation point flow in ferrofluid with Newtonian heating and thermal radiation effect - Siti Hanani, Mat Yasin; Muhammad Khairul Anuar, Mohamed; Zulkhibri, Ismail; Basuki, Widodo; Mohd Zuki, Salleh (Akademi Baru, 2019)
This study aims to investigate MHD stagnation point flow of Magnetite (Fe3O4) with Newtonian heating and thermal radiation effect over a flat plate. The governing equation which is in the form of dimensional nonlinear partial differential equations are reduced to non-linear ordinary equations by using appropriate similarity transformation, then solved numerically by using Keller-box method, which programmed in Matlab software. The influenced of significant parameter such as the magnetic parameter, radiation parameter and volume fraction on velocity and temperature profiles will be obtained. The study reveals the radiation parameter will enhance the temperature of the flow. On the other hand, the skin friction and Nusselt number will increase with an increase magnetic parameter.